Satisfaction with democracy and collective action problems: the case of the environment - Martin Halla; Friedrich G. Schneider; Alexander F. Wagner (Institute for the Study of Labor (IZA), 2008)
Using modern methods for analyzing multi-level data, we find that, by and large, citizens of OECD countries are more satisfied with the way democracy works in their country if more environmental policies are in place and if environmental quality is higher. We also document that parents care about carbon dioxide emissions more than non-parents and that those with a high willingness to pay for environmental quality deplore intervention through government policies.
urn:nbn:de:101:1-2008080737
Keywords: K32; 330; Collective action problems; environmental economics and policy; satisfaction with democracy; Umweltschutz; Umweltpolitik; Demokratie; Meinung; Public Choice; OECD-Staaten